Gatekeepers in Agricultural Extension Research: A Retrospective Analysis - Fallys Masambuka-Kanchewa; Kevan W. Lamm; Alexa J. Lamm (Journal of International Agricultural and Extension Education, 2020)
Social science research plays an important role in transforming agriculture as it provides an invaluable source of information for policy formulation and implementation. Social scientists collecting data in rural communities, where the majority of agricultural production occurs, around the globe frequently pass through a layer of gatekeepers to access research communities and subjects. Gatekeepers serve a critical role in access to subjects but their influence on the research process in many countries and contexts has not been examined thoroughly. The findings of this phenomenology study, conducted in four Sub-Saharan Africa countries, indicated gatekeepers provide invaluable access to individuals and perspectives that may otherwise be inaccessible. However,the findings indicated gatekeepers may also have a vested interests in the research being conducted. Among others, gatekeepers may introduce selection bias to the research process. Therefore, it is important for social scientists working in countries where gatekeepers are involved in the research process to understand the limitations gatekeepers introduce when conducting social science research. Having such knowledge is necessary when interpreting research results and will help researchers be cognizant ofthe power dynamics that may exist between gatekeepers and those they represent as well as implications on the research process
Keywords: Gatekeepers; social science research; objectivity; powerstructures; extension; access; research subjects